2021
DOI: 10.1186/s12302-021-00508-9
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl and polyfluoroalkyl substance exposure and association with sex hormone concentrations: results from the NHANES 2015–2016

Abstract: Background There is increasing global concern regarding the health impacts of perfluoroalkyl and polyfluoroalkyl substances (PFAS), which are emerging environmental endocrine disruptors. Results from previous epidemiological studies on the associations between PFAS exposure and sex hormone levels are inconsistent. Objective We examined the associations between serum PFAS compounds (PFDeA, PFHxS, PFNA, PFOA, PFOS) and sex hormones, including total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Undoubtedly future work is needed to clarify sexually dimorphic effects. 65 In summary, the present study shows that 24-h PFOA exposure in vitro inhibits androgen production but not metabolism in ILCs at physiologically relevant concentrations. 28,[36][37][38]57,58,66,67 Inhibition of androgen biosynthesis is driven by downregulations of LHCGR, CYP11A1, 3β-HSD1, and NR5A1 at both mRNA and protein levels, which correspond with decreased enzymatic activities of CYP11A1 and 3β-HSD1.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Undoubtedly future work is needed to clarify sexually dimorphic effects. 65 In summary, the present study shows that 24-h PFOA exposure in vitro inhibits androgen production but not metabolism in ILCs at physiologically relevant concentrations. 28,[36][37][38]57,58,66,67 Inhibition of androgen biosynthesis is driven by downregulations of LHCGR, CYP11A1, 3β-HSD1, and NR5A1 at both mRNA and protein levels, which correspond with decreased enzymatic activities of CYP11A1 and 3β-HSD1.…”
Section: Discussionmentioning
confidence: 50%
“…It is also notable that PFOA exposure appears to disrupt sex hormones in females in an age‐specific manner. Undoubtedly future work is needed to clarify sexually dimorphic effects 65 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is inconsistent with a 2012-2013 study of cord blood PFAS levels from Shanghai which identified no differences in PFAS concentrations by sex. 34 Other literature, however, suggests that there are sex differences in specific analytes, including PFHxS, at older ages 4345 and outcome-impacting sex-specific associations between PFAS and DNA methylation 33 , an epigenetic regulator of gene expression. No significant sex differences were observed in PFAS concentrations of DBS collected 4 months post-birth, however.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is challenging to present plausible explanations with limited evidence, several potential mechanisms were proposed to explain the NMDR effects of PFAS, including estrogen-like effects, low-dose stimulation effects, and cytotoxicity. PFAS may promote modifications of endogenous hormone regulation in humans and in wildlife [19,[53][54][55]. PFAS showed weak estrogenic effects in animal experiments, which manifested in increased estrogen and progesterone concentrations or mimicked the effect of endogenous estrogen [56][57][58].…”
Section: Discussionmentioning
confidence: 99%